Evaluating the feasibility and preliminary impact of the Social, Emotional, and Ethical (SEE) Learning program: A compassion-based social and emotional learning program for elementary school children - Tyralynn Frazier; Robert W. Roeser; Kimberly A. Schonert-Reichl; Lobsang Tenzin Negi (PLoS ONE, 2025)
Objectives This study aimed to assess the feasibility and preliminary outcomes of the SEE Learning® (Social, Emotional, and Ethical Learning) program among elementary school-aged children. Methodology A quasi-experimental design was employed, with 685 4th- and 5th-grade students across 33 classrooms (344 students received the 12-week SEE Learning program; 341 students were wait-list controls). Assessments of compassion for self and others, social and emotional competencies, and the degree to which students perceived their classrooms as supportive were collected before and after program implementation. Measures of dosage, fidelity, and acceptability were assessed via teachers’ weekly lesson diaries. Results Teachers reported the program was feasible to implement. They demonstrated high lesson completion and fidelity rates with minimal preparation time and strong adherence to the lesson structure. Most program activities fit within a 50-minute timeframe or less, reflecting the program’s suitability for elementary school settings. Student reports showed preliminary impacts of the program. Those who received SEE Learning reported significant improvements in self-compassion, perspective-taking, empathic concern (e.g., compassion for others), intrinsic prosocial motivation, and academic goal setting compared to students in the wait-list control group. Significance This study is among the first to demonstrate the feasibility and preliminary student impacts of the compassion-focused SEE Learning program in an elementary school setting. Future investigations might explore the implementation and effects of the SEE Learning program using randomized-controlled experimental designs and longer-term follow-ups. In addition, studies evaluating program implementation and impacts in diverse cultural-contextual settings, and among students of different ages, are needed. In sum, the SEE Learning program shows evidence of promise for impacting elementary school students’ prosocial skills and competencies.